A wear-resistant, corrosion-resistant, and oxidation-resistant fiber crystal chromium-nitrogen thick film and preparation method thereof

By using a single metal element chromium in surface engineering, a high-hard fiber crystal structure is formed, the problem of nitride coating prone to cracking under high temperature or mechanical wear is solved, and efficient oxidation and wear resistance is achieved, and simplified The process flow reduces pollution and costs.

CN115323324BActive Publication Date: 2024-12-13INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210894364.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-28
Publication Date
2024-12-13
Estimated Expiration
2042-07-28

AI Technical Summary

Technical Problem

The existing nitride coatings are prone to cracking or peeling under high temperature or mechanical wear conditions, making it difficult to achieve effective long-term protection, and the process is complex and polluted, so they cannot take into account both adhesion and performance.

Method used

Using a single metal element chromium, a high-hard directed fiber crystal structure is formed by precisely controlling the reaction process and deposition conditions, and a high-hardness directional fiber crystal structure is prepared, and a fiber crystal chromium nitrogen-based thick film mainly consisting of the Cr2N ceramic phase is prepared, simplifying the process and improving the preparation efficiency.

Benefits of technology

The film layer is achieved with high hardness, excellent oxidation resistance, wear resistance and corrosion resistance, and simple process and low cost. The film layer is well combined with the substrate without cracking or peeling, providing longer-term high-temperature protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115323324B_ABST
    Figure CN115323324B_ABST
Patent Text Reader

Abstract

The present invention provides a wear-resistant, corrosion-resistant and oxidation-resistant fibrous crystal chromium-nitrogen thick film and a preparation method, belonging to the technical field of surface engineering and protective coatings. The thick film layer phase composition is: a Cr2N ceramic phase with a volume fraction greater than or equal to 80%, and an α-Cr metal phase and / or a CrN ceramic phase with a volume fraction less than or equal to 20%, and the Cr2N ceramic phase presents a submicron-level fibrous crystal structure with a highly oriented (300) crystal plane. The preparation steps mainly include sputtering the workpiece surface with high-energy chromium ions under high vacuum conditions, and then using nitrogen ion flow and chromium ion flow to produce molecular clusters with Cr2N as the main phase, which are deposited on the workpiece surface under electric field acceleration to form a hard film layer with a fibrous crystal structure. The chromium-nitrogen thick film of the present invention has excellent antioxidant, wear-resistant and corrosion-resistant properties, a simple preparation process, high preparation efficiency and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface engineering and protective coatings, and in particular relates to a wear-resistant, corrosion-resistant and oxidation-resistant fiber crystal chromium-nitrogen thick film and a preparation method thereof. Background Art

[0002] With the development of industrial technology and the continuous changes in the material application environment, while improving the performance of the material itself, higher and higher requirements are placed on the surface performance of the material. For example, the surface of the material should not only be able to resist wear and erosion, but also have excellent resistance to high temperature oxidation and corrosion. Among them, applying a protective film layer is a more convenient and effective way to protect the surface.

[0003] Nitride coatings have high hardness, good thermal stability, excellent wear resistance, corrosion resistance and oxidation resistance, and play an important role in mechanical processing, mold manufacturing, aerospace and other fields. Increasing the thickness of the coating helps to improve the wear resistance and corrosion resistance of the coating. However, the higher internal stress and intrinsic brittleness of the nitride cause the bonding strength with the substrate to decrease with increasing thickness. It is very easy to crack or peel off during service under high temperature or mechanical wear, making it difficult to achieve effective long-term protection. Therefore, the preparation of thick nitride film layers with strong adhesion and good performance is of great significance in the field of surface protection.

[0004] Chen Wanglin et al. prepared a wear-resistant and corrosion-resistant Cr-PVD composite coating by electroplating and PVD process, that is, firstly electroplating a Cr-plated layer on the substrate surface, then annealing to form a well-bonded diffusion layer, and then PVD depositing nitride on the surface of the Cr-plated layer [see reference: Chen Wanglin, Chen Zhaoxiang, Huang Yonghao, Wu Dayao, A Corrosion-resistant and Wear-resistant Cr-plated PVD Composite Coating and Preparation Method thereof, Patent Publication No.: CN113913736A]. This process is significantly different from the scheme described in the present invention. Although the annealing process used in it enhances the adhesion at the coating interface, the process is complex and discontinuous, resulting in insufficient controllability of the coating quality, easy to form interface contamination in the coating, and serious environmental pollution caused by electroplating, and the technical effect is also insufficient.

[0005] Zhao Haibo prepared a multi-layer nitride thick film for cutting tools, which consists of a transition Cr layer, a multi-layer nitride layer and an AlTiN layer from the inside to the outside. The good ductility and bonding properties of Cr are used to enhance the adhesion of the film base [see document: Zhao Haibo, Thick Film Nitride Coating for Cutting Tools and Its Preparation Method, Patent Publication No.: CN114164405A]. This scheme requires the use of target materials with multiple components to achieve the deposition of the coating, which is essentially different from the scheme described in the present invention.

[0006] Feng Limin et al. used the high entropy effect to prepare an (AlCrTiZrNbV)N coating with both high hardness and excellent corrosion resistance [see reference: A high-hardness and high-corrosion-resistant high-entropy alloy nitride coating, patent publication number: CN108220880A]. The technical solution of adding alloy elements and designing a multilayer structure is essentially different from the solution described in the present invention using a single metal element. Summary of the invention

[0007] The present invention provides a wear-resistant, corrosion-resistant and oxidation-resistant fiber crystal chromium-nitrogen thick film and a preparation method thereof, which uses a single metal element and forms a unique high-hardness oriented fiber crystal structure by precisely controlling the reaction process and deposition conditions, thereby achieving the effects of wear resistance, corrosion resistance and oxidation resistance. The thick film preparation process is simple and the preparation efficiency is high.

[0008] The technical solution of the present invention is as follows:

[0009] A wear-resistant, corrosion-resistant and oxidation-resistant fiber crystal chromium-nitrogen thick film, characterized in that the thick film is a film layer mainly composed of a Cr2N ceramic phase, and the film layer phase composition is: a Cr2N ceramic phase with a volume fraction greater than or equal to 80%, and an α-Cr metal phase and / or a CrN ceramic phase with a volume fraction less than or equal to 20%.

[0010] As the preferred technical solution:

[0011] The film layer phase composition of the thick film has the following three types:

[0012] ① 80%-95% volume fraction of Cr2N ceramic phase and 5%-20% α-Cr metal phase;

[0013] ② Volume fraction of 80%-90% Cr2N ceramic phase and 10%-20% CrN ceramic phase;

[0014] ③ Volume fraction of 80%-95% Cr2N ceramic phase, 5%-20% α-Cr metal phase and CrN ceramic phase.

[0015] The Cr2N ceramic phase is a submicron-scale fiber crystal structure with a highly oriented (300) crystal plane.

[0016] The thick film is composed of an induced seed layer and a main film layer mainly composed of Cr2N ceramic phase, wherein the induced seed layer has a thickness of 0.05-2 microns, preferably 0.1-1 microns, and the main film layer has a thickness of 10-50 microns, preferably 20-35 microns.

[0017] The thick film has a Vickers microhardness in the range of 900-2000 HV, preferably 1200-1800 HV.

[0018] The thick film is 600 oAfter 500h of oxidation in air, the weight gain range is 0.05-0.07mg / cm 2 .

[0019] The present invention also provides a method for preparing the wear-resistant, corrosion-resistant and oxidation-resistant fiber crystal chromium-nitrogen thick film, which is characterized in that the preparation steps are as follows:

[0020] 1) High-energy chromium ion sputtering bombards the workpiece surface under high vacuum conditions to form an induced seed crystal layer on the workpiece surface;

[0021] 2) Nitrogen is introduced and a certain pressure is maintained to form a nitrogen ion flow with a certain volume density. The nitrogen ion flow and the chromium ion flow combine to produce molecular clusters with Cr2N as the main phase, which are deposited on the surface of the workpiece under electric field acceleration to form a dense hard film layer.

[0022] As the preferred technical solution:

[0023] In step 1), the high vacuum condition is ≤0.006Pa, the chromium ion flow is generated by arc discharge of the magnetically confined cathode chromium target, and the nominal arc current density on the target surface is 2.2-3.5A / cm 2 .

[0024] In step 1), the energy of high-energy chromium ions is 400-800 eV, and the surface of the workpiece is sputtered in an intermittent energetic manner to form an induced seed layer. The frequency of the chromium ion acceleration electric field is 5-40 kHz, and the duty cycle is 20-50%.

[0025] In step 2), nitrogen is introduced to maintain its pressure in the range of 0.07-0.25 Pa, and the volume density of the nitrogen ion flow formed is 45-55% of the chromium ion flow.

[0026] In step 2), the chromium ion flow is generated by arc discharge of the magnetically confined cathode chromium target, and the nominal arc current density on the target surface is 1.5-4A / cm 2 ; Accelerating electric field voltage is 100-600V, frequency is 10-40kHz, and duty cycle is 15-60%.

[0027] The beneficial effects of the present invention are:

[0028] The main phase of the thick film of the present invention is a Cr2N ceramic phase. The film layer has high hardness, excellent anti-oxidation, wear resistance and corrosion resistance, and the thick film is well bonded to the substrate. After oxidation and wear tests, the coating structure is still intact without cracking and peeling. The thick film preparation process is simple, the deposition rate is fast, the cost is low, and the protective requirements of wear resistance, corrosion resistance and anti-oxidation can be taken into account. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The surface (a) and cross-section (b) scanning electron microscope photos of the as-prepared chromium-nitrogen thick film.

[0030] Figure 2 XRD pattern of prepared chromium-nitrogen thick film;

[0031] Figure 3 Titanium alloy substrate (a) and chromium nitrogen thick film (b) (b1) at 600 o C Cross-sectional scanning electron microscope photograph after oxidation in air for 500 h;

[0032] Figure 4 The three-dimensional morphology of the wear scar after wear between titanium alloy substrate (a) and chromium-nitrogen thick film (b);

[0033] Figure 5 This is a comparison chart of the wear rate results of titanium alloy substrate and chromium-nitrogen thick film;

[0034] Figure 6 This is the macroscopic morphology of the chromium-nitrogen thick film after 100 days of corrosion in a standard salt spray environment;

[0035] Figure 7 This is the XRD pattern of the prepared film layer in the comparative example. DETAILED DESCRIPTION

[0036] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments:

[0037] Example 1

[0038] The method of preparing wear-resistant, corrosion-resistant and oxidation-resistant fiber crystal chromium-nitrogen thick film by multi-arc ion plating is described as follows:

[0039] 1) Install the pure chromium target in a cathode water-cooled target sleeve with magnetic field constraints, fix the selected titanium alloy substrate on the sample holder, close the vacuum chamber, and evacuate the air; when the vacuum degree of the chamber back reaches 0.006Pa or lower, use the contact method to directly ignite the cathode arc with the arc needle. First, deposit the induced seed layer to enhance the film-base bonding strength. In this example, the arc current density is 2.5A / cm 2 , chromium ion energy 400eV, frequency 40kHz, duty cycle 20%, chromium ion flow bombardment 2min.

[0040] 2) Then, nitrogen gas is introduced to form a nitrogen ion flow and a chromium ion flow through the chromium plasma zone to compositely deposit a chromium-nitrogen thick film. In this example, the nitrogen pressure is 0.1 Pa and the arc current density is 2.5 A / cm 2 , accelerating electric field 100V, frequency 40kHz, duty cycle 20%, deposition 2h.

[0041] The surface and cross-sectional scanning photos of the prepared chromium-nitrogen thick film are shown in Figure 2. Figure 1As shown in the figure, the coating surface is smooth and uniform, with small molten droplets scattered here and there. The coating thickness is about 30 microns, the coating structure is dense and well bonded to the substrate. Figure 2 The XRD results show that the main phase of the chromium-nitrogen thick film is a Cr2N ceramic phase with a highly oriented (300) crystal plane, and the thick film is composed of about 5% α-Cr metal phase and about 95% Cr2N ceramic phase. The hardness of the film is 1600HV.

[0042] High temperature oxidation performance: bare titanium alloy substrate and chromium nitrogen thick film were heated at 600 o C was oxidized in air for 500h. The cross-sectional morphology after oxidation is as follows Figure 3 As shown in the figure, it can be seen that the thickness of the oxide film generated by the chromium-nitrogen thick film is only 0.6 microns, which is much lower than the thickness of the oxide film on the surface of the titanium alloy (8.3 microns). The oxidation weight gain of the chromium-nitrogen thick film is only 0.062 mg / cm 2 , while the oxidation weight gain of the matrix is ​​1.33 mg / cm 2 , indicating that the film has excellent oxidation resistance. At the same time, the chromium nitrogen thick film is still well bonded to the substrate after oxidation, no cracking occurs, the film structure is complete and crack-free, and can provide longer high-temperature protection.

[0043] Wear performance: The wear test was carried out on the equipment MFT-5000, using Si3N4 balls as counter grinding balls, normal load 10N, frequency 2Hz, sliding length 6mm, and wear time 20min. Figure 4 The three-dimensional morphology of the wear scar of the titanium alloy substrate and the chromium-nitrogen thick film after wear is shown. It can be seen that the titanium alloy substrate is severely worn, the wear scar is wide and deep, and the wear scar depth is as high as 20 microns. In contrast, the wear surface of the chromium-nitrogen thick film is nearly flat. Figure 5 The wear rate of the titanium alloy substrate and the chromium-nitrogen thick film layer was displayed. The results showed that the wear rate of the film layer was only 0.4% of that of the substrate, which shows that the coating effectively improved the wear performance of the substrate.

[0044] Corrosion resistance: The samples coated with chromium-nitrogen thick film were placed in a salt spray chamber for room temperature salt spray corrosion test. Figure 6 This is the macroscopic morphology of the sample after being placed for more than 100 days. The surface of the film still maintains a bright metallic color and no rust spots appear, indicating that the film has excellent corrosion resistance at room temperature.

[0045] Example 2

[0046] Multi-arc ion plating is used to prepare wear-resistant, corrosion-resistant and oxidation-resistant fiber crystal chromium-nitrogen thick film:

[0047] 1) Install the pure chromium target in a cathode water-cooled target sleeve with magnetic field constraints, fix the selected titanium alloy substrate on the sample holder, close the vacuum chamber, and evacuate the air; when the vacuum degree of the chamber back reaches 0.006Pa or lower, use the contact method to directly ignite the cathode arc with the arc needle. First, deposit the induced seed layer to enhance the film-base bonding strength. In this example, the arc current density is 3A / cm 2 , the chromium ion energy is 500eV, the frequency is 40kHz, the duty cycle is 20%, and the chromium ion flow bombardment is 2min.

[0048] 2) Then, nitrogen gas is introduced to form a nitrogen ion flow and a chromium ion flow through the chromium plasma zone to compositely deposit a chromium-nitrogen thick film. In this example, the nitrogen pressure is 0.2 Pa and the arc current density is 3 A / cm 2 , accelerating electric field 100 V, frequency 20kHz, duty cycle 25%, deposition 2h. The main phase of the prepared chromium-nitrogen thick film is a Cr2N ceramic phase with a highly oriented (300) crystal plane. The thick film composition is about 10% CrN ceramic phase and about 90% Cr2N ceramic phase. The film hardness is 1850HV. The obtained film is 600 o The thickness of the oxide film formed after oxidation in air for 500 hours is 0.57 microns, and the oxidation weight gain is 0.06 mg / cm 2 , showing excellent oxidation resistance. Using Si3N4 balls as grinding balls, under the wear conditions of normal load 10N, frequency 2Hz, sliding length 6mm, and wear time 20min, the wear rate of the film layer is only 0.3% of the corresponding bare titanium alloy substrate, showing excellent wear resistance. After up to 100 days of room temperature salt spray corrosion test, the film layer still maintains a bright metallic color and no rust spots appear, indicating that the film layer has excellent room temperature corrosion resistance.

[0049] Example 3

[0050] Multi-arc ion plating is used to prepare wear-resistant, corrosion-resistant and oxidation-resistant fiber crystal chromium-nitrogen thick film:

[0051] 1) Install the pure chromium target in a cathode water-cooled target sleeve with magnetic field constraints, fix the selected titanium alloy substrate on the sample holder, close the vacuum chamber, and evacuate the air; when the vacuum degree of the chamber back reaches 0.006Pa or lower, use the contact method to directly ignite the cathode arc with the arc needle. First, deposit the induced seed layer to enhance the film-base bonding strength. In this example, the arc current density is 2.5A / cm 2 , the chromium ion energy is 500eV, the frequency is 30kHz, the duty cycle is 30%, and the chromium ion flow bombardment is 2min.

[0052] 2) Then, nitrogen gas is introduced to form a nitrogen ion flow and a chromium ion flow through the chromium plasma zone to compositely deposit a chromium-nitrogen thick film. In this example, the nitrogen pressure is 0.15 Pa and the arc current density is 3 A / cm 2, accelerating electric field 200V, frequency 20kHz, duty cycle 30%, deposition 2h.

[0053] The main phase of the prepared chromium-nitrogen thick film is a Cr2N ceramic phase with a highly oriented (300) crystal plane. The thick film composition is: about 10% by volume of α-Cr metal phase + CrN ceramic phase, and about 90% of Cr2N ceramic phase. The film hardness is 1680HV. The obtained film is 600 o The thickness of the oxide film formed after oxidation in air for 500 hours is 0.7 microns, and the oxidation weight gain is 0.068 mg / cm 2 , showing excellent oxidation resistance. Using Si3N4 balls as counter-grinding balls, under the wear conditions of normal load 10N, frequency 2Hz, sliding length 6mm, and wear time 20min, the wear rate of the film layer is only 0.5% of the corresponding bare titanium alloy substrate, showing excellent wear resistance. After up to 100 days of room temperature salt spray corrosion test, the film layer still maintains a bright metallic color and no rust spots appear, indicating that the film layer has excellent room temperature corrosion resistance.

[0054] Comparative Example

[0055] The film layer mainly composed of α-Cr metal phase is prepared by multi-arc ion plating:

[0056] 1) Install the pure chromium target in a cathode water-cooled target sleeve with magnetic field constraints, fix the selected titanium alloy substrate on the sample holder, close the vacuum chamber, and evacuate the air; when the vacuum degree of the chamber back reaches 0.006Pa or lower, use the contact method to directly ignite the cathode arc with the arc needle. First, deposit the induced seed layer to enhance the film-base bonding strength. In this example, the arc current density is 2A / cm 2 , the chromium ion energy is 450eV, the frequency is 20kHz, the duty cycle is 25%, and the chromium ion flow bombardment is 3min.

[0057] 2) Then, nitrogen gas is introduced to form a composite deposition film layer of nitrogen ion flow and chromium ion flow through the chromium plasma zone. In this example, the nitrogen pressure is 0.03Pa and the arc current density is 2A / cm 2 , accelerating electric field 200V, frequency 30kHz, duty cycle 30%, deposition 2h.

[0058] Figure 7 The XRD results show that the main phase of the prepared film is α-Cr metal phase. The hardness of the film is 265HV. Using Si3N4 balls as counter grinding balls, under the wear conditions of normal load 10N, frequency 2Hz, sliding length 6mm, and wear time 20min, the wear rate of the film is 120% of the corresponding bare titanium alloy substrate, and the wear resistance is poor.

[0059] Matters not covered by the present invention are known technologies.

[0060] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a wear-resistant, corrosion-resistant and oxidation-resistant fiber crystal chromium-nitrogen thick film, characterized in that: The preparation steps are as follows: 1) High-energy chromium ion sputtering bombards the workpiece surface under high vacuum conditions to form an induced seed crystal layer on the workpiece surface; 2) Nitrogen is introduced and a certain pressure is maintained to form a nitrogen ion flow with a certain volume density. The nitrogen ion flow and the chromium ion flow combine to produce molecular clusters with Cr2N as the main phase, which are deposited on the surface of the workpiece under electric field acceleration to form a dense hard film layer; In step 1), the high vacuum condition is ≤0.006Pa, the chromium ion flow is generated by arc discharge of the magnetically confined cathode chromium target, and the arc flow density on the target surface is 2.2-3.5A / cm 2 ; In step 1), the energy of the high-energy chromium ions is 400-800 eV, and the surface of the workpiece is sputtered intermittently to form an induced seed layer, the frequency of the chromium ion acceleration electric field is 5-40 kHz, and the duty cycle is 20-50%; In step 2), nitrogen is introduced to maintain its pressure range of 0.07-0.25 Pa, and the volume ratio of the nitrogen ion flow formed is 45-55% of the chromium ion flow; In step 2), the chromium ion flow is generated by arc discharge of the magnetically confined cathode chromium target, and the arc flow density on the target surface is 1.5-4A / cm 2 ; Accelerating electric field voltage 100-600V, frequency 10-40kHz, duty cycle 15-60%; The Cr2N ceramic phase is a submicron-scale fibrous crystal structure with a highly oriented (300) crystal plane; The thick film is composed of an induced seed crystal layer and a main film layer mainly composed of a Cr2N ceramic phase, wherein the induced seed crystal layer has a thickness of 0.05-2 microns; the main film layer has a thickness of 10-50 microns; The main film layer has a phase composition of: a Cr2N ceramic phase with a volume fraction greater than or equal to 80%, and an α-Cr metal phase and / or a CrN ceramic phase with a volume fraction less than or equal to 20%; The Vickers microhardness of the thick film is in the range of 900-2000 HV; the oxidation weight gain of the thick film after oxidation in air at 600°C for 500 hours is in the range of 0.05-0.07 mg / cm 2 .